Transition strategies for hospital discharge used by nurses: integrative review - Valéria Cristina Lopes Gallo; Daiana Kloh Khalaf; Karina Silveira de Almeida Hammerschmidt; Mariane Lima Santiago; Carine Vendruscolo (Universidade Federal de Santa Maria, 2021)
Objective: to identify strategies for the transition of care at hospital discharge, used by nurses to strengthen the continuity of care, available in the scientific literature. Method: integrative review of the literature, which included complete studies, based on the strategies "care transition" OR "Continuity of Patient Care" OR "care continuity" AND nurse for the databases VHL, PubMed, SCOPUS and WoS and "care transition" OR "care continuity" AND nurse for CINAHL , published in English, Spanish or Portuguese, between 2016 and 2020, which answered the review question. Results: 23 articles were selected, and the strategies for transition from care to hospital discharge used by nurses to strengthen care were health education, drug reconciliation, telemonitoring, discharge planning, counter-referral and home visit. Conclusion: nurses are responsible for developing interconnected transition strategies to strengthen care, developing diversified actions that qualify attention.